MANAJEMEN PESERTA DIDIK DALAM UPAYA MENINGKATKAN MUTU LULUSAN DI SMA NEGERI 3 PANYABUNGAN KABUPATEN MANDAILING NATAL - Tamimi, Zulpadli; Ali Yusron; Sapirin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Student management in educational institutions plays an important role, because students are the main component in the input, process, and output of education. In SMA Negeri 3 Panyabungan, effective student management contributes to quality educational outcomes. Therefore, there is a need for optimization in student management to support the achievement of educational goals, both curricular (related to subjects), institutional (related to institutions), and national education goals. This study aims to: 1) Describe the principal's student management planning in improving the quality of graduates at SMA Negeri 3 Panyabungan. 2) Describe the implementation of student management in improving the quality of graduates at SMA Negeri 3 Panyabungan 3) Determine the supporting and inhibiting factors of student management in efforts to improve the quality of graduates at SMAN 3 Panyabungan. This study uses qualitative research. The research procedures used produce data in the form of written words, oral expressions from informants. Informants in this study were 1 principal, 3 class teachers, 1 guidance and counseling teacher with 4 students. The results of the study show that student management in an effort to improve the quality of graduates at SMAN 3 Panyabungan is said to be good in accordance with the results of research at the planning stage of good student management to produce quality alumni. This is also proven by the number of student output percentages each year at this school, as many as 80% continue and pass at state universities, and 20% of students continue to enter the workforce.